International food safety standards and South Africa’s orange exports to key Asian markets: An analysis based on the gravity model using three-dimensional data - Phaleng, Lucius Tshwene; Hlongwane, Jan Johannes; Nkoana, Mmaphuti Andrias (International Journal of Innovative Research and Scientific Studies, 2025)
This paper aims to analyze the impact of food safety regulations imposed by strategic Asian countries on South Africa’s orange exports to these markets. The analysis employed a gravity model with three-dimensional data from 2003 to 2022. The model indicates that the influence of descriptive variables is significant with an f-statistic significant at the 1% level and an adjusted R-squared of 0.580 suggesting that variables account for a considerable share of variation in orange exports. It was revealed that an increase in the importer’s GDP of 1% decreases South Africa’s export performance while a rise in South Africa’s GDP enhances it. Population growth positively influences export volumes. Furthermore, the exchange rate volatility at the 5% level supports rather than hinders export growth suggesting resilience within the industry. Notably, TBT measures positively and significantly influence orange exports contrary to fears that food safety issues might impede exports. In contrast, the insignificant and negative coefficient for SPS measures suggests a counterproductive effect on South African orange exports about food safety standards. Findings highlight crucial factors that affect and enhance South Africa's orange export growth providing important insights for policymakers and stakeholders in the agricultural export sector to navigate food safety regulations and optimize export strategies.